1997
DOI: 10.1128/jvi.71.10.7442-7447.1997
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA encoding replicating foot-and-mouth disease virus genomes induces antiviral immune responses in swine

Abstract: DNA vaccine candidates for foot-and-mouth disease (FMD) were engineered to produce FMD virus (FMDV) particles that were noninfectious in cell culture or animals. The prototype plasmid, pWRM, contains a cytomegalovirus immediate-early promoter-driven genome-length type A12 cDNA followed by the bovine growth hormone polyadenylation site. BHK cells transfected with this plasmid produced virus, but the specific infectivity of pWRM was much lower than that achieved with in vitro-generated RNA genomes. To improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(16 citation statements)
references
References 43 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…co-expression) of viral proteases, but not the VP1 protein by itself, can elicit a significant level of neutralizing antibodies and confer an effective level of protection against viral challenge with FMDV. Previous studies have shown that the whole virus particle or an 'authentic' empty capsid assembly was very important for induction of neutralizing antibodies and protection against viral challenge [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…co-expression) of viral proteases, but not the VP1 protein by itself, can elicit a significant level of neutralizing antibodies and confer an effective level of protection against viral challenge with FMDV. Previous studies have shown that the whole virus particle or an 'authentic' empty capsid assembly was very important for induction of neutralizing antibodies and protection against viral challenge [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Mason and colleagues have developed two types of DNA vaccine against the FMDV serotype A12 [21][22][23]. One contains a full-length cDNA of the FMDV genome and the other a cDNA construct containing the P1-2A and 3C (proteases) encoding regions which have been shown to elicit neutralizing antibody and have partially protected test pigs against viral infection [21][22][23]. According to these cDNA constructs, it seems that capsid formation in situ is required for effective immunization [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that a fundamentally different type of DNA vaccine, based on production of attenuated full-length viral genomes in inoculated animals can also stimulate an anti-FMDV immune response (36). The DNA vaccine candidate presented here has some safety advantages over the construct developed by Ward et al (36), since only empty viral particles are synthesized in vaccinated animals.…”
mentioning
confidence: 92%
“…We have recently shown that a fundamentally different type of DNA vaccine, based on production of attenuated full-length viral genomes in inoculated animals can also stimulate an anti-FMDV immune response (36). The DNA vaccine candidate presented here has some safety advantages over the construct developed by Ward et al (36), since only empty viral particles are synthesized in vaccinated animals. In addition, animals inoculated with piP12X3C, which lacks the coding regions for several nonstructural viral proteins, can be distinguished from virus-infected animals, which show immune responses to these antigens (5,24).…”
mentioning
confidence: 92%
“…Nevertheless, vaccination still remains contentious owing to its limitations. For example, conventional inactivated virus vaccines may leave residual live virus in vaccines, DNA vaccines elicit inadequate neutralizing antibody to protect against the disease in swine (Balamurugan et al, 2004;Ward et al, 1997), chimeric vaccines have possibilities to lead to production of virulent viruses and to a lack of thermostability for inactivated vaccine production (Van Rensburg and Mason, 2002) and so on. Furthermore, it is imperative to use a new antiviral strategy to compensate vaccine's requirement of at least 7 days to induce protection while the clinical disease and infectivity appear in infected animals as early as 2-3 days post-exposure .…”
Section: Introductionmentioning
confidence: 99%